2008
DOI: 10.1590/s0004-282x2008000600032
|View full text |Cite
|
Sign up to set email alerts
|

Normal hearing after resection of a large vestibular schwannoma

Abstract: Advances in anesthesia and surgical techniques have brought the surgical mortality rate for vestibular schwannomas (VS) to less than 1% [1][2][3] . Increased preservation rates of facial and cochlear function were observed in the most recent large series by Samii et al.1 . Nevertheless, preservation of House-Brackmann grade I and Hannover Class H1 (PTA <20dB and SDS >95%) hearing function postoperatively after total removal of large tumors is still a challenge, even in experienced hands 1,2,[4][5][6] . Our obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…We used multishell HCP data to create the template, which is of high quality with minimal distortion artifacts and a small voxel size of 1.25 Â 1.25 Â 1.25 mm. 3 Second, we found that deterministic tractography is more suitable than probabilistic tractography in creating the FVN template. In this study, we mainly forced on the cisternal portion of the FVN and the portion just entering the brainstem that does not have a large bend.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…We used multishell HCP data to create the template, which is of high quality with minimal distortion artifacts and a small voxel size of 1.25 Â 1.25 Â 1.25 mm. 3 Second, we found that deterministic tractography is more suitable than probabilistic tractography in creating the FVN template. In this study, we mainly forced on the cisternal portion of the FVN and the portion just entering the brainstem that does not have a large bend.…”
Section: Discussionmentioning
confidence: 85%
“…1 The FVN controls facial expression 2 and hearing. 3 Tumor 4 and intraoperative inadvertent injury may lead to FVN dysfunctions, such as paralysis, impaired facial function, 5 and hearing loss, 6 or psychological issues. 7 The aim of surgical treatment is to excise tumors totally while preserving FVN function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation